Efecto del Comercio Internacional sobre la desigualdad, evidencia empírica para 110 países agrupados de acuerdo a su nivel de ingreso, periodo 1982-2015 - Loján Hualpa, David Alexander (2020)
The role of income inequality continues to play an important role in threats, since its increase has repercussions on macroeconomic, institutional and social variables. In this context, this document examines the effect of international trade on inequality, empirical evidence for 110 countries grouped according to their level of income, period 1982-2015. To meet the objective of this applied research, four economic techniques: generalized least squares (GLS), Westerlund cointegration model (2007), totally modified ordinary least squares (FMOLS) by Phillips and Hansen (1990); and, finally, the Granger causality test proposed by Dumitrescu and hurlin (2012). The changing results in international trade generate immediate changes in inequality; however, in the long term, there is no stable relationship, since beta parameters are not conclusive in any group of countries. On the other hand, the causality test shows that there is a one-way causal relationship of inequality towards trade globally. For this reason, the policy implications are aimed at fighting inequality between nations, by protecting national production with import tariff mechanisms, avoiding the outflow of foreign exchange with a tax burden, especially in underdeveloped countries. Keywords: Inequality. International Trade. Cointegration Panel data. JEL classification: D63. F14. C23.